Communication Behaviour of Farmers Adopting Rice Fallow Pulse Technologies - Sundaram, Parthasarathi; Alauddin, A. Shaik (Journal of Extension Education, 2018)
A study was conducted to assess the communication behaviour of farmers adopting recommended rice fallow pulse crop technologies in Karaikal district. Karaikal district is a part of Union Territory of Puducherry located in the tail end of Cauvery delta zone where most of the farmers follow the rice fallow pulse crop with the availabe moisture, which fetches more income to them. The communication behaviour was studied under two dimensions viz., information source utilisation and information sharing behaviour. Correlation was worked out to assess the contribution of communication behaviour in the knowledge and adoption of rice fallow pulse technologies. In the case of regular contact, group members, neighbours and family members were the major sources of information. Information source utilization and information sharing were significant in their relationship with knowledge level of farmers whereas information sharing of farmers alone contributed positively to the adoption of technologies.